Makna Shirat, Sabil Dan Thariq Dalam Tafsir Al-Misbah Serta Implementasinya Dalam Kehidupan - Ebing Karmiza (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
The problem raised in this paper is how the meaning of shirat, sabil and tariq in the Qur'an with a semantic approach and its implementation in life. Then how the meaning of the word in the interpretation of al-Misbah, how the linguistic features and what methods are used, it will be seen textually different from those contained in the interpretation of al-Misbah. The purpose of writing this thesis is to find out how the meaning of the three words above in the interpretation of al-Misbah with a semantic approach. This research is a type of library research or library, which is based on two sources, namely primary sources (the Holy Qur'an and the interpretation of al-Misbah) and secondary sources (supporting books related to the subject). Then after the data is collected, the data will then be grouped according to subtitles. The theoretical conclusion in this discussion shows that the word sabil refers more to the way of guidance or guidance which means one path of truth, while the sabil way of guidance which still provides the choice of truth or error is where the human ability to choose. As for the word Tariq, it means more broadly, can walk, position and others